Art therapy as an activity to support the process of opening up to the Other - Majewska-Owczarek, Anna (Granice tolerancji w sztuce i w wychowaniu, 2020)
The aim of the article is to look at art-therapeutic activities from a new perspective and present them as an area in which, apart from changing the image of the reality and creating a new way of self-awareness, there is also an attitude of openness towards the Other. The Otherness in the article is considered in the category of a difference, which appears between people in a direct relationship. Each relationship is associated with the occurrence of various tensions, with the clash of different points of view, sometimes with crossing one’s own borders, which is why it is legitimate to look for solutions that can help to build understanding between people. The article presents examples of creative workshops on various topics. Based on their analysis and the experience of the art therapy researcher, the article attempts to answer the questions whether art therapy contributes to shape a new perspective and openness to the Other and whether it is possible to determine the moment during art-therapeutic activities in which this openness occurs. Problems for further exploration were also formulated.